How Does Learning Affect Inflation After a Shift in the Exchange Rate Regime? - Papi, Laura (IMF Working Papers; Working Paper ;, 1994)
This paper analyzes the consequences of a shift from a floating to a pegged exchange rate regime on the actual and expected inflation rate, in an environment of asymmetric information. Policymaking is endogenous and the public learns rationally. There are two main findings. First, there is a 'honeymoon effect' after the regime change, where inflation is lower than in the long run. Second, the asymmetric information outcome converges to that of symmetric information in the long run.